Evaluasi Tingkat Kedisiplinan Dalam Kepatuhan Pekerja Pada Kawasan Industri - Maulana, Faisal; Rahmawati, Vivi; Rahayu, Agustina Puji; Oktobery, -; Pramana, Asteria Narulita; Ratnasari, Ardiana Vita (Jounal of Enviromental Science Sustainable, 2023)
The purpose of the research is to evaluate the level of discipline among industrial workers through a literature review of several national and international journals published from 2016 to 2024. The method used is a literature review by analyzing 20 relevant journals, which include qualitative, quantitative, descriptive, empirical legal research, and the Analytical Hierarchy Process (AHP) method. The research results show that employee discipline is a component that can influence productivity and work effectiveness in the industry. Discipline encompasses aspects of attendance, adherence to regulations, work ethics, as well as the attitudes and motivation of workers. The results of this study conclude that companies need to implement employee discipline evaluations that can positively contribute to performance at both the individual and overall company levels. Work discipline is greatly influenced by internal factors such as motivation, attitude, and the desire of workers to excel, as well as external factors such as employment status, reward and punishment systems, leadership role models, and a supportive work environment. Routine evaluation of discipline is very important for workers, especially for new employees who lack experience.